Value Innovation in the Malaysian Telecommunications Service Industry: Case Study - Hajar, Mohamed A.; Daing Nasir, Ibrahim; Al-Sharafi, Mohammed A. (Springer Nature, 2019)
Wireless telecommunications industry has been widely known for its high levels of innovativeness and competitively dynamic business environment. Globalization, privatization, liberalization and consolidation are the terms mostly associated with this sector. The Malaysian telecommunications industry is of no exception for it has exhibited high levels of competitiveness and dynamic change leading to rapid evolution of wireless technologies and high growth of subscribers and penetration rate. Thus, this paper aims to shed some light on the logic of value innovation in the telecommunication service industry. The present study adopted a qualitative research approach to investigate the value innovation activities on Malaysian telecommunications service sector. Specifically, it concentrates on the motivation of telecommunications companies to shift their strategies from tariff competition to value competition in order to improve customer value and promote customer loyalty which lead to increased business performance and profitable growth. An analytical case study was used to examine services and loyalty packages offered by telecommunications companies. In this regard, the paper discusses the shortfalls and actions that discouraged customer satisfaction and loyalty. The paper also provides recommendations for service providers on how to attain long-term profitable growth.